2016
DOI: 10.1177/0961203316676384
|View full text |Cite
|
Sign up to set email alerts
|

Time trend and risk factors of avascular bone necrosis in patients with systemic lupus erythematosus

Abstract: Objectives The objective of this paper is to study the time trend and risk factors of avascular bone necrosis (AVN) in patients with systemic lupus erythematosus (SLE). Methods Between 1999 and 2014, patients who fulfilled the ACR criteria for SLE and developed symptomatic AVN were identified from our cohort database and compared with those without AVN, matched for age, sex and SLE duration. The standardized incidence ratios (SIRs) of AVN in different SLE age groups were calculated from data derived from our h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
3

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 35 publications
1
29
3
Order By: Relevance
“…Due to the retrospective nature of our study, the incidence is a little lower than the previous study (8.9%) [10]. Unlike the lower rates of osteonecrosis in renal allograft recipients (3.4%) [6], our results are comparable to the prevalence of osteonecrosis in other diseases treated with corticosteroids, such as SLE [4,11]. Higher dose of corticosteroid in MM patients and immunosuppressive agents using such as cyclosporin or tacrolimus in renal transplantation may contribute to the result.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…Due to the retrospective nature of our study, the incidence is a little lower than the previous study (8.9%) [10]. Unlike the lower rates of osteonecrosis in renal allograft recipients (3.4%) [6], our results are comparable to the prevalence of osteonecrosis in other diseases treated with corticosteroids, such as SLE [4,11]. Higher dose of corticosteroid in MM patients and immunosuppressive agents using such as cyclosporin or tacrolimus in renal transplantation may contribute to the result.…”
Section: Discussioncontrasting
confidence: 41%
“…Among them, osteonecrosis of femoral head (ONFH) is a rare adverse event in patients undergoing systemic corticosteroid treatment but one with considerable possibility of disability [3]. While corticosteroid-induced ONFH has been reported extensively in systemic lupus erythematosus, renal transplantation, and leukemia patients [4][5][6], there are few studies to identify the incidence and risk factors for ONFH in MM patients.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been found that disease severity of SLE is associated with AVN. 13,14,18,22,23 Especially, several studies have reported that proliferative lupus nephritis was associated with corticosteroid-associated damage such as AVN. 13,23,39,40 Since high-dose steroid use and induction therapy of immunosuppressants (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…15 Although the reported predictive factors of AVN have varied among different reported studies, corticosteroid use has been widely considered to be one of the important ones. 8,10,[12][13][14][16][17][18] However, AVN can occur in patients who have not used steroids, 19,20 furthermore, the incidence of AVN was found to be higher in SLE patients than in non-SLE patients requiring steroid therapy, 17 supporting the roles of several factors specific to SLE. In addition to corticosteroid use, it has been reported that renal disease, neuropsychiatric manifestation, serositis, arthritis, presence of antiphospholipid antibodies, and use of immunosuppressive agents are associated with AVN in SLE in various studies.…”
Section: Introductionmentioning
confidence: 98%
“…We were interested to read the paper written by Tse and colleagues published in Lupus in 2017. 1 The authors aimed to evaluate the time trend and risk factors of avascular bone necrosis (AVN) in patients with systemic lupus erythematosus (SLE). One of the main findings was that preceding septic arthritis of the involved joint was independently associated with AVN [odds ratio (OR) = 17.7; 95% confidence interval (CI): 1.5–205].…”
mentioning
confidence: 99%